2002
DOI: 10.1093/embo-reports/kvf012
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and identification of essential gene functions on the X chromosome of Drosophila

Abstract: The Drosophila melanogaster genome consists of four chromosomes that contain 165 Mb of DNA, 120 Mb of which are euchromatic. The two Drosophila Genome Projects, in collaboration with Celera Genomics Systems, have sequenced the genome, complementing the previously established physical and genetic maps. In addition, the Berkeley Drosophila Genome Project has undertaken large-scale functional analysis based on mutagenesis by transposable P element insertions into autosomes. Here, we present a large-scale P elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 30 publications
(28 reference statements)
3
109
0
2
Order By: Relevance
“…The polar pigmentation phenotype was also seen in omb insertion of white + -marked gene disruption elements such as P(XP) or piggyBacWH. 41 Several insertions from the screens of Peter et al (2002) 39 and Tang and Sun (2002), 40 reported to be independent, clustered to identical positions. Remarkably, the insertion omb P14 lies just 108 bp downstream of the upstream flanking gene CG3626 (which according to FlyAtlas is expressed in an unrelated pattern 42 ) but more than 40 kb upstream of the omb transcription start site (TSS).…”
Section: Resultsmentioning
confidence: 99%
“…The polar pigmentation phenotype was also seen in omb insertion of white + -marked gene disruption elements such as P(XP) or piggyBacWH. 41 Several insertions from the screens of Peter et al (2002) 39 and Tang and Sun (2002), 40 reported to be independent, clustered to identical positions. Remarkably, the insertion omb P14 lies just 108 bp downstream of the upstream flanking gene CG3626 (which according to FlyAtlas is expressed in an unrelated pattern 42 ) but more than 40 kb upstream of the omb transcription start site (TSS).…”
Section: Resultsmentioning
confidence: 99%
“…P{lacW}G0237 (Peter et al 2002), mis12 PBac{WH}f03756 (Thibault et al 2004), and the Df(3L)BSC27, Df(3L)BSC224 deficiencies were obtained from the Bloomington Stock Center. Stocks for Df(1)52 and Dp(1:Y)B s-v 1 y 1 (Meller and Rattner 2002) were kindly provided by Victoria Meller.…”
Section: Methodsmentioning
confidence: 99%
“…P-element induced lethal mutations on the X and third chromosomes were obtained from the Bloomington Drosophila Stock Center. The X chromosome collection consisted of 398 stocks that included most lethal alleles generated in the original Pelement mutagenesis screen (Peter et al 2002). The third chromosome collection consisted of 467 lethal P-element insertions characterized and reduced to a unigene set by the Berkeley Drosophila Genome Project (Bellen et al 2004).…”
Section: Methodsmentioning
confidence: 99%